Expression of NEAT1 induced by influenza virus infection is regulated by activated STAT3 and contributes to STAT3-mediated antiviral immunity - Gu, Rongrong; Xu, Erying; Hong, Jingjie; Fan, Liqing; Liu, Shasha; Chen, Ji-Long (Frontiers in Immunology, 2025)
The transcription factor STAT3 is integral to the immune response during viral infections, while long non-coding RNAs (lncRNAs) are actively implicated in the modulation of viral pathogenesis. However, the relationship between STAT3 and lncRNAs during viral infection is poorly understood. Here, we observed that robust expression of NEAT1, an important lncRNA, was induced by infections with influenza A virus (IAV) and several other viruses, but the virus-induced NEAT1 expression was significantly suppressed by inactivation of STAT3 both in vitro and in vivo. Furthermore, we identified that expression of NEAT1 was regulated via MDA5 and TLR3 signaling pathways involving NF-κB, IL-6, and IFN-β during IAV infection. Disruption of NEAT1 expression markedly facilitated the replication of IAV, whereas overexpression of NEAT1 attenuated the viral replication. NEAT1 knockout mice were further employed and showed that deficiency of NEAT1 significantly enhanced the IAV replication and virulence in the animals. Importantly, we found that activation of STAT3 by innate immune signaling inhibited IAV infection through upregulating the expression of NEAT1, and NEAT1 promoted the production of several vital antiviral molecules including interferons (IFNs) to suppress the viral replication. Moreover, our experiments exhibited that NEAT1 contributed to activation of TBK1 during the IAV infection. Together, these results reveal that NEAT1 functions downstream of STAT3, acting as a regulator of STAT3-mediated immunity by activating TBK1 and thereby enhancing antiviral responses.